Cohabitation, infection and breast cancer risk. Issue 6 (26th October 2020) - Kinlen, Leo J.; Gilham, Clare; Ray, Roberta; Thomas, David B.; Peto, Julian
Abstract: For 50 years, the effect of age at first birth (AFB) has been thought to explain the strong association between breast cancer risk and age at first marriage (AFM), which was first reported in 1926. The independent effects of AFM, AFB and number of sexual partners adjusted for parity and other risk factors were estimated in reanalysis of a large international case‐control study conducted in 1979 to 1982 (2274 breast cancers, 18209 controls) by unconditional logistic regression. Respective AFB and AFM breast cancer odds ratios (ORs) for ≥31 years relative to ≤18 years were 3.01 (95% CI 2.44‐3.71; P (trend) < .0001) and 3.24 (95% CI 2.62‐4.01; P (trend) < .0001) in univariate analyses. Among married parous women, these ORs fell to 1.38 (95% CI 0.98‐1.95; P (trend) < .03) for AFB and 1.70 (95% CI 1.17‐2.46; P (trend) < .002) for AFM when fitted together in multivariate analysis including other risk factors. A similar adjusted OR for AFM ≥ 31 years relative to ≤18 years was seen among married nulliparous women (OR 1.71, 95% CI 0.98‐2.98; P (trend) < .001). AFM (a surrogate for age at starting prolonged cohabitation) is thus strongly associated with breast cancer risk. This suggests an effect of close contact. Identifying the (probably infective) mechanism might lead to effective prevention of breast cancer. The independent effect of AFB is smaller and could be due to residual confounding. What's new?: Early investigations of breast cancer risk factors identified potential associations with age at first marriage (AFM) and age at first birth (AFB). Here, reanalysis of data from the WHO Collaborative Study of Neoplasia and Steroid Contraceptives (1979‐82) suggests that AFM, a surrogate for age at beginning cohabitation, is strongly associated with breast cancer risk in parous and nulliparous women. The effect of AFB, a long‐accepted breast cancer risk factor, appears to be due largely, and perhaps entirely, to confounding. This surprising conclusion warrants further study, along with investigation of underlying infective mechanisms as possible targets for breast cancer prevention.